Germination Response of the Epiphytic Cactus Rhipsalis baccifera (J. S. Miller) Stearn to Different Light Conditions and Water Availability - Edilia De la Rosa Manzano; Oscar Luis Briones Villarreal (International Journal of Plant Sciences, 2010)
In the forest canopy, seeds of epiphytic plants encounter heterogeneous environments created by a combination of factors such as solar radiation, humidity, and host characteristics. Germination requirements may explain the species distribution in the canopy; however, more knowledge is essential. Germination of Rhipsalis baccifera, a widespread tropical epiphytic cactus and representative of the humid montane forest in Mexico, was 80% or higher with far red, red, and white light and close to 0 in darkness. Germination was light saturated at very low photon flux density of only 13.5 mmol m 2 s 1. Germination decreased gradually at low water potentials and with increased storage time. After storage for 1 yr, no seeds germinated. Seeds have the ability to germinate in both the internal and external positions of the tree crowns. The germinative requirements of R. baccifera indicate that it could colonize a wide range of light conditions in the canopy; however, substrate humidity and seed age could limit germination.